Clinical Profile and Consequences of Atrial Fibrillation in Hypertrophic Cardiomyopathy. Issue 25 (19th December 2017) - Rowin, Ethan J.; Hausvater, Anais; Link, Mark S.; Abt, Patrick; Gionfriddo, William; Wang, Wendy; Rastegar, Hassan; Estes, N. A. Mark; Maron, Martin S.; Maron, Barry J.
Abstract : Background: Atrial fibrillation (AF), the most common sustained arrhythmia in hypertrophic cardiomyopathy (HCM), is capable of producing symptoms that impact quality of life and is associated with risk for embolic stroke. However, the influence of AF on clinical course and outcome in HCM remains incompletely resolved. Methods: Records of 1558 consecutive patients followed at the Tufts Medical Center Hypertrophic Cardiomyopathy Institute for 4.8±3.4 years (from 2004 to 2014) were accessed. Results: Of the 1558 patients with HCM, 304 (20%) had episodes of AF, of which 226 (74%) were confined to symptomatic paroxysmal AF (average, 5±5; range, 1 to >20), whereas 78 (26%) developed permanent AF, preceded by 7±6 paroxysmal AF episodes. At last evaluation, 277 patients (91%) are alive at 62±13 years of age, including 89% in New York Heart Association class I or II. No difference was found in outcome measures for patients with AF and age- and sex-matched patients with HCM without AF. Four percent of patients with AF died of HCM-related causes (n=11), with annual mortality 0.7%; mortality directly attributable to AF (thromboembolism without prophylactic anticoagulation) was 0.1% per year (n=2 patients). Patients were treated with antiarrhythmic drugs (most commonly amiodarone [n=103] or sotalol [n=78]) and AF catheter ablation (n=49) or the Maze procedure at surgical myectomy (n=72). Freedom from AF recurrence at 1 year was 44% for ablation patients and 75% with the Maze procedure ( P <0.001). Embolic events were less common with anticoagulation prophylaxis (4/233, 2%) than without (9/66, 14%) ( P <0.001). Conclusions: Transient symptomatic episodes of AF, often responsible for impaired quality of life, are unpredictable in frequency and timing, but amenable to effective contemporary treatments, and infrequently progress to permanent AF. AF is not a major contributor to heart failure morbidity or a cause of arrhythmic sudden death; when treated, it is associated with low disease-related mortality, no different than for patients without AF. AF is an uncommon primary cause of death in HCM virtually limited to embolic stroke, supporting a low threshold for initiating anticoagulation therapy. Abstract : Supplemental Digital Content is available in the text.